Pemberdayaan Masyarakat Lokal Dalam Memanfaatkan Peluang Ekonomi Media Sosial - Nurmasari Situmeang; Shanti Darmastuti; R. Maisa Yudono; Syahrul Salam (CV. Multi Kreasi Media, 2026)
The development of digital technology has transformed social media into a major catalyst for the economic empowerment of local communities. However, this potential is often hampered by the lack of public understanding of effective digital marketing strategies, which result in many local businesses still using the platform conventional and trapped in a medium-dominated commercial system. This community service activity aims to empower PKK mothers in Desa Mekarjaya, Sukabumi, Jawa Barat, by utilizing social media as a self-distribution channel. The implementation method uses a participatory-educative approach, with pre-test and post-test assessments to measure the increase in knowledge. Pre-test results show that the majority of participants have never received training on the economic benefits of social media and most use it only to communicate. Through extension, participants are taught practical strategies such as the technique of taking photos of products using mobile phones, creating persuasive product descriptions, and active communication to build customer trust. Materials are emphasized on the importance of recognizing the peculiarities of local products and consistent in posting to build a credible digital track record. Results showed significant improvement in participants’ understanding; the majority of respondents had understood the economic benefits of social media and considered it an effective new market for local business promotion, particularly local food. The activity successfully cuts the long distribution chain, enabling PKK mothers to control their product prices, increase profit margins, and build sustainable financial independence. Continuous mentoring is required to improve technical skills and further innovation.